2018
DOI: 10.1039/c7ra13347b
|View full text |Cite
|
Sign up to set email alerts
|

A density functional study on the reactivity enhancement induced by gold in IrAu nanoalloys

Abstract: The effects of chemical ordering on the stability and chemical reactivity on IrAu NAs of different sizes (8, 27, 48 and 64 total atoms) and compositions are studied using DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Experimental and theoretical studies agree that for Ir−Au nanoparticle segregation is energetically favored over mixing. 39,40,55,56 It was also found that these bimetallic nanoparticles exhibit a surface structure that is much closer to (100) than to (111) surfaces. 39 In order to emulate the structure of these nanoparticles, we focus our study on Ir, Au, and Ir−Au (100) surfaces.…”
Section: ■ Theoretical Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Experimental and theoretical studies agree that for Ir−Au nanoparticle segregation is energetically favored over mixing. 39,40,55,56 It was also found that these bimetallic nanoparticles exhibit a surface structure that is much closer to (100) than to (111) surfaces. 39 In order to emulate the structure of these nanoparticles, we focus our study on Ir, Au, and Ir−Au (100) surfaces.…”
Section: ■ Theoretical Methodsmentioning
confidence: 97%
“…39,40,55,56 It was also found that these bimetallic nanoparticles exhibit a surface structure that is much closer to (100) than to (111) surfaces. 39 In order to emulate the structure of these nanoparticles, we focus our study on Ir, Au, and Ir−Au (100) surfaces. All of them were modeled with four-layer slabs periodic along the x and y axes.…”
Section: ■ Theoretical Methodsmentioning
confidence: 97%
See 1 more Smart Citation